PEOPLES’ PERCEPTIONS ON THE IMPACTS OF VEGETATION COVER CHANGES ON HUMAN HEALTH: LESSONS FROM PLAGUE INFESTED AREAS OF WEST USAMBARA HIGHLANDS, TANZANIA - Riziki S.SHEMDOE (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2023)
Human plague in West Usambaras, northeast Tanzania, has been a public health problem for many years. Incidences of plague have been associated with various practices in agriculture, forestry and natural catastrophes. In west Usambaras, due to the reduction of vegetation cover, different ecosystem management practices have been carried out. The impact of these practices on creation of rodent’s hiding places and consequently outbreaks of plague and the socio-economic importance of these practices, were not well documented. The broad objective of this study was therefore to investigate the perceptions of local communities on the impacts of vegetation cover changes on human health using lessons from plague infested areas of West Usambaras, Tanzania. Methodologically, Participatory Rural Appraisal (PRA) and individual household questionnaire surveys were applied in data collection. PRA was used prior to questionnaire administration. Primary data from households were collected using structured questionnaires containing both open and close-ended questions. While qualitative data were analysed by content analysis, Statistical Package for Social Sciences (SPSS) was used to analyse quantitative data. The results showed that, planting of guatemala grass (Tripsacum laxum), elephant grass (Pennisetum purpureum), banana, sugarcane and trees, terrace making and zero grazing were identified as ecosystem management practices that were carried out to improve the vegetation cover in the area from the serious deforestation resulted from the over population in the area. However it was also shown that fodder grasses mainly guatemala grass to be affiliated with the provision of shelter for rodents and hence created close contact between human beings and the wild rodents which has been brought about by the dependence of these grasses by both human being for their livestock and the wild rodents as a shelter, the contacts that increased the possibility of spreading of the plague disease in the area. Introduction of ecosystem management education in primary schools, establishment of tree nurseries in schools and villages, emphasis on tree planting by communities and upkeep of zero grazing, were recommended as appropriate measures to be adopted in preserving ecosystem and reduce shelter for rodents close to human settlements.